Finn and the intergalactic lunchbox - Buckley, Michael, 1969- ([Finniverse series], 2020)
"When Earth is threatened by an invading race of bugs called the Hunger, 11-year-old Finn, his arch-nemesis, Lincoln, his crush, Julep, and one pink unicorn lunchbox become Earth's last best hope against destruction"--